Treatment of Bottom Ash Medical Waste (BAMW) from Hospital Infectious Waste into Paving Block Products - Riyanto, Riyanto; Asrel; Jatnika, Yuda (EKSAKTA: Journal of Sciences and Data Analysis, 2024)
Hospital solid waste is infectious waste, so it is included in the category of hazardous and toxic waste. One method of processing hospital solid waste is by burning it in an incinerator. The result of burning B3 waste at high temperatures is ash or known as bottom ash medical waste (BAMW). Ash from hospital waste processing is included in hazardous and toxic materials, so it needs to be handled properly. This study aims to process BAMW using the solidification/stabilization method. The BAMW processing product is paving blocks. The study was conducted by varying the composition of paving blocks. The variations carried out were the percentage of BAMW and its particle size. In addition, a Total Organic Carbon (TOC) level test was carried out on the water used to soak the paving blocks after being stored for 27 days. The results of the study showed that the higher the percentage of BAMW, the lower the compressive strength of the paving blocks, while the ability to absorb water and wear increased. The size of the BAMW particles also affects the quality of the paving blocks. The smaller the particle size, the better the quality of the paving blocks. Higher compressive strength indicates better quality of the paving blocks. The results of the analysis of the water used to soak the paving blocks showed that the TOC concentration was higher if the compressive strength decreased. BAMW can be used as an additional material for making paving blocks, but the composition should not be large.